Killer-cell immunoglobulin-like receptor diversity in an admixed South American population - Castrillon, Marlon; Marin, Nancy D.; Karduss-Urueta, Amado J.; Velásquez, Sonia Y.; Alvarez, Cristiam M. (Cells, 2022)
Natural Killer (NK) cells are innate immune cells that mediate antiviral and antitumor responses. NK cell activation and induction of effector functions are tightly regulated by the integration of activating and inhibitory receptors such as killer immunoglobulin-like receptors (KIR). KIR genes are characterized by a high degree of diversity due to presence or absence, gene copy number and allelic polymorphism. The aim of this study was to establish the distribution of KIR genes and genotypes, to infer the most common haplotypes in an admixed Colombian population and to compare these KIR gene frequencies with some Central and South American populations and worldwide. A total of 161 individuals from Medellin, Colombia were included in the study. Genomic DNA was used for KIR and HLA genotyping. We analyzed only KIR gene-content (presence or absence) based on PCR-SSO. The KIR genotype, most common haplotypes and combinations of KIR and HLA ligands frequencies were estimated according to the presence or absence of KIR and HLA genes. Dendrograms, principal component (PC) analysis and Heatmap analysis based on genetic distance were constructed to compare KIR gene frequencies among Central and South American, worldwide and Amerindian populations. The 16 KIR genes analyzed were distributed in 37 different genotypes and the 7 most frequent KIR inferred haplotypes. Importantly, we found three new genotypes not previously reported in any other ethnic group. Our genetic distance, PC and Heatmap analysis revealed marked differences in the distribution of KIR gene frequencies in the Medellin population compared to worldwide populations. These differences occurred mainly in the activating KIR isoforms, which are more frequent in our population, particularly KIR3DS1. Finally, we observed unique structural patterns of genotypes, which evidences the potential diversity and variability of this gene family in our population, and the need for exhaustive genetic studies to expand our understanding of the KIR gene complex in Colombian populations.